(untitled) (Eurasian Journal of Ecology, 2016)
This work contains research , which searched natural feed lands’ plant cover of Berikkarin rural district of Zhambyl region with the aim to use it efficient , protect them, develop recommendations. During the research ecological conditions of area were defined, plant cover structure , typological structure, territorial distribution of land types, area, productivity, quality of feed, contemporary use of natural feed grasslands and opportunity of using them were revealed. Research work had 3 steps (preparation, field and laboratory). General area of Berikarin rural district is 40589 hectare, in this researched territory 127 types of plant which refer to 30 families were defined.